Positional differences in some physiological parameters obtained by the incremental field endurance test among elite handball players (Kinesiology, 2021)
The purpose of the study was to assess assumed differences in some physiological parameters, obtained by an incremental intermittent running field test 30–15IFT, among elite handball players to get an insight into the specifics of aerobic capacity profiles of players in different playing positions. Twenty-four elite male handball players were tested using the Cosmed K4 portable telemetry system. The following parameters were analysed: running velocity, heart rate, oxygen uptake, relative oxygen uptake, pulmonary ventilation breath-by-breath, at the three points—lactate threshold (LT), onset of blood lactate accumulation (OBLA), and at the peak velocity achieved on the test (v30–15IFT). Additionally, blood lactate concentration was analysed at v30–15IFT. The players were divided in three groups based on their playing positions: eight backcourt players, eight wing players and eight pivot players. In terms of both the statistically significant and non-significant differences, the wings achieved slightly different results in comparison to the backcourt players and pivots. The wings reached a statistically significant higher velocity at the LT than the players of the other two groups and a significantly higher velocity than the pivots at the OBLA. At all the three points, wings presented the highest HR values, meaning they can operate at higher intensities still within the aerobic work zone. This would probably allow wing players to longer persist in handball game.Key words: team handball, playing positions, aerobic incremental field test, men